Identification of independent risk factors for skin complications in a multifactorial logistic regression analysis of simultaneous immediate autologous breast reconstruction and skin reduction mastectomy in large and ptotic breasts using an inferiorly based deepithelialized dermal breast flap - Vollbach, Felix Hubertus; Thomas, Benjamin; Fansa, Hisham (Journal of Personalized Medicine, 2022)
Autologous immediate breast reconstruction in large and ptotic breasts remains challenging. We aimed to identify independent risk factors for impaired wound healing and nipple necrosis after skin reducing wise pattern mastectomy in autologous reconstruction with an auxiliary deepithelialized inferiorly based dermal flap (IBDF). Methods. This retrospective study examined patients with wise pattern mastectomy with autologous immediate breast reconstruction (IBR) between 2017 and 2019. All cases of large and ptotic breasts were included. Demographic, oncologic, reconstructive, and surgical data were compiled, and multifactorial binary logistic regression models identified independent predictors for skin complications and nipple areolar complex (NAC) necrosis. Results. Of 591 autologous breast reconstructions, 62 (11%) met the inclusion criteria. Overall wound complication rate was 32% (n = 20, DIEP 11, thigh 9, p = 0.99), including 26% minor (n = 16, non-surgically treated) and 7% major complications (n = 4, surgically treated). Complete NAC necrosis occurred in one case. Nipple sparing mastectomy (NSM) (p = 0.003), high BMI (p = 0.019), longer operation time (p = 0.044) and higher patient age (p = 0.045) were independent risk factors for skin complications. Using internal mammary artery perforators (IMAP) as recipient vessels did not result in increased complication rates (p = 0.59). Conclusion. Higher patient age, BMI, and operation time (OT) significantly increase the risk for skin complications in combined reduction wise pattern mastectomies with autologous IBR. In this context, IBDFs help preserve the inframammary fold, providing vasculature to the T-junction and the mastectomy skin flaps. Acceptable complication rates can be achieved in large and ptotic breasts, regardless of preoperative chemotherapy or radiation. Gentle tissue handling with minimal thermal trauma preserves internal mammary artery perforators (IMAPs) as recipient vessels. In cases of flap failure and alloplastic conversion, the IBDF can serve as an autoderm, protecting the implant from exposure
Gesehen am 14.05.2022